Removal of a 3' non-coding sequence is an initial step in degradation of gro alpha mRNA and is regulated by interleukin-1. - Stoeckle, M Y (1992)
I have previously shown that IL-1 regulates the stability of gro alpha mRNA in fibroblasts and that decay is associated with appearance of a smaller species of gro RNA that lacks poly(A). In this study, the relationship between the two species of gro RNA, which migrate at 1.3 and 0.9 kilobases, was characterized. Following withdrawal of IL-1 or addition of IL-1 receptor antagonist, 1.3 kilobase gro alpha mRNA was rapidly degraded and this was associated with increased expression of the 0.9 kilobase RNA. This increase occurred in the presence of actinomycin D, indicating that the 0.9 kilobase gro RNA was a product of a pre-existing transcript. In cells treated with 1 pg/ml IL-1, both species were induced but the 0.9 kilobase RNA appeared later, consistent with a precursor-product relationship. In cells treated with higher doses of IL-1, the 0.9 kilobase RNA was not expressed. Using an RNAase protection assay, the 0.9 kilobase poly(A)-minus gro RNA was found to be derived from gro alpha mRNA by removal of a 130-nucleotide sequence from the 3' non-coding region. This is one of few examples of formation of an mRNA decay intermediate in vivo; it indicates that degradation of the body of gro alpha mRNA is initiated by site-specific nuclease attack. Characterization of the mechanism of gro alpha mRNA degradation is a first step towards identification of the ribonuclease that controls gro alpha mRNA stability.